2022
DOI: 10.1371/journal.pntd.0009900
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequences of Treponema pallidum subsp. endemicum isolated from Cuban patients: The non-clonal character of isolates suggests a persistent human infection rather than a single outbreak

Abstract: Bejel (endemic syphilis) is a neglected non-venereal disease caused by Treponema pallidum subsp. endemicum (TEN). Although it is mostly present in hot, dry climates, a few cases have been found outside of these areas. The aim of this work was the sequencing and analysis of TEN isolates obtained from “syphilis patients” in Cuba, which is not considered an endemic area for bejel. Genomes were obtained by pool segment genome sequencing or direct sequencing methods, and the bioinformatics analysis was performed ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As syphilis has been the central focus of Treponema research, the endemic treponematoses have received less attention 2 , 40 . Contrary to yaws and syphilis, both of which have been previously found in Old and New World contexts from the early modern period 3 6 , this newly reconstructed genome represents the first TEN-like pathogen isolated from archaeological remains, and the only ancient comparison to the current set of eight published bejel genomes 17 , 38 , 41 , 42 . Recent cases have shown that treponematoses are occasionally transmitted in an atypical manner for their genetically confirmed subspecies, and have challenged their geographical and symptom-driven categorizations 43 45 .…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…As syphilis has been the central focus of Treponema research, the endemic treponematoses have received less attention 2 , 40 . Contrary to yaws and syphilis, both of which have been previously found in Old and New World contexts from the early modern period 3 6 , this newly reconstructed genome represents the first TEN-like pathogen isolated from archaeological remains, and the only ancient comparison to the current set of eight published bejel genomes 17 , 38 , 41 , 42 . Recent cases have shown that treponematoses are occasionally transmitted in an atypical manner for their genetically confirmed subspecies, and have challenged their geographical and symptom-driven categorizations 43 45 .…”
Section: Discussionmentioning
confidence: 70%
“…We selected all eight publicly available TEN genomes, all of which have more than 99.4% genome coverage, with the exception of C77 17 (81.4%). We selected 30 TPE genomes (Supplementary Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the final phylogenetic analyses, genes identified by PIM as recombinant were excluded from the multiple genome alignment. To avoid introducing a potential bias into the phylogenetic signal, 3 genes ( tp0897, tp0316, tp0317 ), which contain repetitive regions and have previously been reported as hypervariable and/or under gene conversion (Pinto et al 2016; Liu et al 2019;Addetia et al 2020); (Strouhal et al 2018; Vrbová et al 2022) and thus induce recombination-like effects in mapping, were also removed. As the tp0317 gene is embedded inside the tp0316 gene, and moreover the coordinates from the BosniaA reference genome for tp0316 spanned a longer region compared to the other reference genomes, tp0316 and tp0317 were removed according to the BosniaA reference genome coordinates for tp0316 .…”
Section: Methodsmentioning
confidence: 99%